Orexins/Hypocretins: Key Regulators of Energy Homeostasis - Milbank, Edward; López, Miguel (Frontiers in Endocrinology, 2019)
Although they were initially described to be involved in feeding regulation, orexins/hypocretins are now also considered as major regulatory actors of numerous biological processes, such as pain, sleep, cardiovascular function, neuroendocrine regulation and energy expenditure. Therefore, they constitute one of the most pleiotropic families of hypothalamic neuropeptides. Although their orexigenic effect is well documented, orexins/hypocretins central effects on energy expenditure, notably on the brown adipose tissue (BAT) thermogenesis, remain still unclear. A better comprehension of the underlying mechanisms and potential interactions with other hypothalamic molecular pathways involved in the modulation of food intake and thermogenesis, such as AMP-activated protein kinase (AMPK) and endoplasmic reticulum (ER) stress, is essential to determine the exact implication and pathophysiological relevance of orexins/hypocretins on the control of energy balance. Here, we will review the actions of orexins on energy balance, with focus on feeding and brown fat function.